2016
DOI: 10.1136/sextrans-2015-052456
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic HPV-related neovaginal lesions in transgender women: case series and review of literature

Abstract: Neovaginal HPV infection can lead to benign condylomata (lrHPV) and various grades of dysplasia (hrHPV). We advise physicians to consider HPV infection and associated lesions in transgender women with otherwise unexplainable neovaginal pain or bleeding after vaginoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…Histological changes may occur because the grafted tissue is subject to new stressors, such as exposure to semen or micro-injuries during intercourse exposing the basal membrane, the primary binding site for HPV. The vulnerability of particular tissues to HPV infections and premalignant changes remains unclear, as only case studies of dysplasia and neovaginal cancers have been published [ 2 5 ]. It is suggested that squamous cell cancers occur in skin-graft neovaginas, whereas adenocarcinomas occur in intestinal neovaginas [ 2 , 4 ], but most reports have not investigated MRKH patients operated with Davidov’s method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological changes may occur because the grafted tissue is subject to new stressors, such as exposure to semen or micro-injuries during intercourse exposing the basal membrane, the primary binding site for HPV. The vulnerability of particular tissues to HPV infections and premalignant changes remains unclear, as only case studies of dysplasia and neovaginal cancers have been published [ 2 5 ]. It is suggested that squamous cell cancers occur in skin-graft neovaginas, whereas adenocarcinomas occur in intestinal neovaginas [ 2 , 4 ], but most reports have not investigated MRKH patients operated with Davidov’s method.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the literature on the prevalence of HPV positivity in neovaginas is limited [ 3 , 5 , 6 ], but the rate of occurrence seems similar to that in the general population [ 6 ]. The present case demonstrated that serial HPV infections may also occur in MRKH women.…”
Section: Discussionmentioning
confidence: 99%
“…16 Like all keratinized skin, the neovagina is also susceptible to HPVinduced dysplasia. 45 When intestinal vaginoplasty is performed, the neovagina is lined with intestinal, often ileal, mucosal tissue. HPV-related penile cancer is less common than colorectal and anal cancers, making the risk of cancer theoretically higher in neovaginas lined with colonic mucosa compared with neovaginas lined with keratinized penile shaft skin.…”
Section: Cervical Cancermentioning
confidence: 99%
“…A few benign conditions have also been reported in the neovaginas of transgender women. Several studies have demonstrated the presence of condyloma accuminata in transgender women, mainly in neovaginas constructed from penile and scrotal tissues (Brown et al, 2015, Galea et al, 2015, Nureña et al, 2013, van der Sluis et al, 2016). These lesions can present with coital pain and bleeding (van der Sluis et al, 2016).…”
Section: Benign Neovaginal Diseasementioning
confidence: 99%